Plantar Pressure Distribution among Older Persons with Different Types of Foot and Its Correlation with Functional Reach Distance - Aisyah Mohd Said; Maria Justine; Haidzir Manaf (Scientifica)
Background. Changes in biomechanical structures of human foot are common in the older person, which may lead to alteration of foot type and plantar pressure distribution. We aimed to examine how foot type affects the plantar pressure distribution and to determine the relationship between plantar pressure distribution and functional reach distance in older persons. Methods. Fifty community-dwelling older persons (age: 69.98±5.84) were categorized into three groups based on the Foot Posture Index. The plantar pressure (max⁡P) and contact area were analyzed using Footscan® RSScan platform. The Kruskal-Wallis test was used to compare the plantar pressure between foot types and Spearman’s correlation coefficient was used to correlate plantar pressure with the functional reach distance. Results. There were significant differences of max⁡P in the forefoot area across all foot types. The post hoc analysis found significantly lower max⁡P in the pronated foot compared to the supinated foot. A high linear rank correlation was found between functional reach distance and max⁡P of the rearfoot region of the supinated foot. Conclusions. These findings suggested that types of the foot affect the plantar maximal pressure in older persons with functional reach distance showing some associations.